Real‐life efficacy and safety of glecaprevir/pibrentasvir in HCV‐infected patients with chronic kidney disease. Issue 4 (3rd July 2019) - Persico, Marcello; Aglitti, Andrea; Caruso, Rosa; Calvanese, Gemma; Di Siervi, Pasqualina; Masarone, Mario; ,
Summary: Background: Clinical trials have shown that glecaprevir/pibrentasvir (G/P) therapy is effective and safe for HCV‐infected patients with chronic kidney disease (CKD), but data in a real‐life setting are scarce. Aim: To evaluate the efficacy and safety of G/P in HCV‐infected patients with reduced renal function. Patients and Methods: All consecutive HCV‐infected patients with CKD (eGFR <60 mL/min/1.73 m 2 ) treated with G/P were enrolled. An adverse event (AE) was defined as any untoward medical occurrence or any unfavourable sign or symptom, during drug administration that was not necessarily causally treatment‐related. An AE causing death, hospitalisation or therapy discontinuation was considered a serious AE (SAE). Results: A total of 121 patients were enrolled. Thirty‐six patients had end‐stage renal disease (ESRD), 57 were male, overall median age was 69 ± 13 years and 20 had cirrhosis. Genotype 2 was the most frequent (53.7%). Treatment lasted 8 weeks in 93 patients, 21 of whom had ESRD, and 12 weeks in 28 patients. At modified intention‐to‐treat analysis, 119/120 patients achieved a sustained virologic response (SVR) without differences between cirrhotics and non‐cirrhotics, whereas at per protocol analysis all patients achieved a SVR. Notably, SVR did not differ between patients with and without ESRD (35/35 vs 84/85 P  = 0.427). There were no virologic failures. Thirteen patients reported an AE (mostly pruritus), three had a SAE (death in a car accident and two jaundice) and one spontaneously stopped treatment. Conclusion: This real‐life study confirms the high efficacy and safety of G/P, also administered for 8 weeks, in HCV‐infected patients with CKD or with ESRD.